Structural transformation behavior of oxide scale during coiling of 0.9 wt% Cr-containing high-strength steel - Chao Wang; Huibin Wu; Youyou Zhang (Journal of Materials Research and Technology, 2024)
The phase transformation mechanism of oxide scale on the surfaces of chromium (Cr)-free carbon steel and 0.9 wt% Cr-containing steel at different coiling temperatures and cooling rates was studied using thermal simulation and electron backscattering diffraction experiments. The results showed that the eutectoid transformation of both the steel followed the “C” curve relationship. The Cr-containing steel had a larger eutectoid transformation area fraction than the Cr-free carbon steel. The nose tip temperature of the eutectoid transformation of the oxide scale on the surfaces of Cr-free carbon steel and 0.9 wt% Cr-containing steel were 420∼510 °C and 420–480 °C, respectively. For the 0.9 wt% Cr-containing steel, the proportion of Σ3 and Σ13b grain boundaries in cubic Fe3O4 increased, followed by a decrease, when the coiling temperature decreased from 610 to 410 °C. The Σ3 and Σ13b grain boundaries of the Fe3O4 low-dimensional coincident site lattice had the highest proportion for 510 °C coiling temperature. The low-dimensional coincident site lattice grain boundaries could be used to enhance crack resistance and improve the oxide scale on the steel plate surface.